Security and privacy in social network - Mohammad Izzat Mohammad Noor (2014)
Social Network has experienced a boom in the World Wide Web (WWW) in the recent years. This has resulted in an increase in the number of users all around the world. This increase in users has led to the rise in issues on privacy and security. Although there have been some research in the aforementioned issues, it is still in its infancy stage and various examples either lack in the security aspect or social network features. This project aims to build an independent privacy and security preserving social network which is able to maintain the integrity and confidentiality of the users’ data through the use of cryptographic schemes such as ElGamal and AES encryptions. With this design, users are able to protect the privacy and integrity of their data from potential attackers, while also preserving the availability, reliability and usability benefits of a current social network. The implementation has allowed data confidentiality, integrity, non-repudiation, data authentication and unauthorised access to information.